Bahasa Indonesia: Bahasa Indonesia - Heni Herlina; Yulvia Sani (Jurnal Pendidikan Kebutuhan Khusus, 2018)
Research in the background of an inclusive X school that has not yet had a special tutor, children with special needs have not been handled properly. One of them is that there are autistic children who experience tantrums, if their desire is not fulfilled the child will tantrum. This is because the programs run in schools with at home do not go hand in hand. The research method used is a two-stage research, the first stage uses a qualitative approach with descriptive method and the second stage uses a quantitative approach with the method of subject subject reseach. The results of the research at stage one that children often experience tantrum behavior in the classroom, so that parents cannot handle properly, parents tend to follow all their children's wishes. Then for phase two a training program for parents will be given on how to apply the rules in the classroom. Based on the parents' empowerment program in handling tantrums, autistic children in X inclusive schools are very effective because of changes in tantrum behavior of autistic children from before being given intervention after the intervention